Analisis Nilai-Nilai Kearifan Lokal Tokoh Utama dalam Novel Anak Rantau Karya Ahmad Fuadi dengan Pendekatan Objektif - Ismanto Ismanto (Universitas Palan, 2024)
This research analyzes the local wisdom values contained in the novel Anak Rantau by Ahmad F in using an objective approach. An objective approach is used to understand the meaning and message contained in the literary work without influencing the analysis with the researcher's subjective views. The purpose of this research is to identify Ahmad Fuadi's ideas in nasi and describe the local wisdom values ​raised by him. Through in-depth textual analysis, it was found that this novel contains various local wisdom values such as mutual cooperation, respect for parents, perseverance, and honesty. Apart from that, Minangkabau cultural values such as the basandi syarak custom, syarak basandi kitabullah, and the importance of education are also very prominent in the story. These values are not only characteristic of the culture adopted by the author, but also make a significant contribution in shaping the character and morality of the characters. Thus, the novel Anak Rantau not only functions as an entertaining literary work but also as an educational medium that introduces and emphasizes the importance of local wisdom in everyday life.